A multi-criteria decision making approach for responsible rural tourism - Nair, Madhavan Balan; Ramachandran, Sridar; Nair, Vikneswaran (2011)
Involvement of multiple stakeholders in the decision making process for sustainable tourism cannot be denied. The tourism sector increasingly being pressured by policy makers and tourist demand to be more responsible in carrying out their activities. This is evident in rural tourism setting where tourist expectation demands experience of tourism activities in their natural setting. Rural tourism has been there for sometime but responsible rural tourism (RRT) practice are still at its infancy in Malaysia. Local communities have begun to demand for increased income and preservation of local values. These increased awareness and pressure requires a clear framework for stakeholders who operate in this rural setting to be more responsible in carrying out their activities. At present, in Malaysia RRT guidelines for authorities and business operators remain ambivalent. RRT indicators from stakeholders perspective need to be identified to assist in the decision making process. Indicators such as water quality, economic impact, social impact to local community, environmental degradation will be examined. Stakeholders are faced with a multi-criteria decision making process that will be explored in this research paper. This research aim is to explore the suitability of a multi-criteria decision making model for stakeholders to make decision with inclusion of all necessary indicators/criteria. The model is expected to assist decision makers in making calculated decision towards being responsible in rural tourism practices. RRT implementation is a complex problem and therefore requires a holistic means in approaching it. A multi-criteria approach is therefore significant to address the problem using critical realism as a theoretical lens that supports the use of mixed method design. A mixed method approach enables the blend of qualitative and quantitative approach enables the blend of qualitative and quantitative approach. The qualitative data is important to explore the current decision making practice of business operators, especially their perception towards stakeholder participation. The quantitative approach is required to extract the indicator values for the decision making tool.